Pengaruh Inflasi, Suku Bunga, dan Kurs Terhadap Harga Saham (Studi Pada Perusahaan Sub Sektor Makanan dan Miniman Yang Terdaftar Di BEI) - Astutik, Astutik; Lilianti, Emma; Jusmani, Jusmani (Jurnal Media Akuntansi (Mediasi), 2024)
ABSTRACT The aims of this study were (1) to determine the role of inflation on stock prices (a study on food and beverage subsector companies listed on the IDX, (2) to determine inflation on stock prices). stock prices (a study of food and beverage subsector companies) (3) The effect of the exchange rate on stock prices (a study of food and beverage subsector companies) listed on the IDX, (4) Determination of the effect of inflation, interest rates and exchange rates on stock prices together with stock prices The research method used is a quantitative method which can be understood as a method based on the philosophy of positivism, used to investigate a particular population or sample.The aims of this study were (1) to determine the role of inflation on stock prices (a study on food and beverage subsector companies listed on the IDX, (2) to determine inflation on stock prices). stock prices (a study of food and beverage subsector companies) (3) The effect of the exchange rate on stock prices (a study of food and beverage subsector companies) listed on the IDX, (4) Determination of the effect of inflation, interest rates and exchange rates on stock prices together with stock prices The research method used is a quantitative method which can be understood as a method based on the philosophy of positivism, used to investigate a particular population or sample. Keywords: Financial Performance, Financial Ratio, PSAK72 ABSTRAK Penelitian ini bertujuan (1) mengenal peranan inflasi terdapat harga saham (tentang perkembangan yang bergerak di bidang food and drink yang sudah terdaftar di Bursa Efek Indonesia., (2) mengetahui dampak inflasi terhadap harga saham). harga saham (studi pada perusahaan subsektor makanan dan minuman (3) Penentuan pengaruh nilai tukar terhadap harga saham (studi pada perusahaan subsektor makanan dan minuman) makanan dan minuman yang terdaftar di BEI, ( 4) Menentukan pengaruh Inflasi, Suku Bunga dan Kurs yang menentukan harga saham secara bersama-sama terhadap harga saham Metode penelitian yang digunakan adalah metode kuantitatif, yang dapat dipahami sebagai metode yang didasarkan pada filosofi positivisme, yang digunakan dalam berbagai penelitian terhadap populasi atau sampel tertentu. Kata kunci: Kinerja Keuangan, Rasio Keuangan, PSAK72.